Integrated Front-End Approaches for Wireless 100 Gb/s and Beyond: Enabling Efficient Ultra-High Speed Wireless Communication Systems - Carlowitz, Christian; Dietz, Marco (IEEE Microwave Magazine, 2023)
Wireless communication faces ever-growing demand for higher data rates, which has driven the need for modem implementations that are capable of providing single-link data rates on the order of 100 Gb/s and beyond for extremely fast data transmission. In recent years, the 60-GHz band has been employed to significantly increase wireless local area network data rates in IEEE’s 802.11ad standard targeting multigigabit modems. Its extension 802.11ay was finalized in 2021, targeting data rates toward 100 Gb/s in the same bands by increasing spectral efficiency and combining up to four channels with more than 8-GHz bandwidth in total [1] . This approach has the advantage of existing unlicensed regulatory allocations. Nevertheless, options for higher bandwidth have increasingly been investigated, also driven by the publication of the IEEE 802.15.3d [2] physical layer standard for a frequency range between 252 and 325 GHz, which resides in an atmospheric window that enables reasonable long-range communication links on the order of a few kilometers. In this frequency range, a substantially higher bandwidth is achievable. Specific regulatory allocations are still missing; nevertheless, the conditions to use this frequency range have already been discussed and described during the 2019 World Radiocommunication Conference [3] . Although the first demonstrations of 100-Gb/s modems in this frequency range were at least partially based on photonic technologies [4] , integrated front ends in different semiconductor technologies have been demonstrated [5] and are discussed in the present article in more detail together with the major remaining challenges for practical applications.<br
Keywords: Wireless communication; Wireless LAN; Spectral efficiency; Bandwidth; Modems; Transceivers; Resource management